การนำเสนอแนวทางการจัดการศึกษาตลอดชีวิตในพิพิธภัณฑ์ดนตรี - จิรัฏฐา จารุพิสิฐธร (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
The purposes of this research were to study the current situations, problems and needs of lifelong education management in music museums and to propose guidelines for lifelong education management in music museums. The data were collected using the interview questionnaire in current situations, problems and needs of the three music museums and music learning resources, and other three sets of questionnaires for gathering 12 experts’ opinions of lifelong education, museum management and music, then analyzed the data through median, mode, median-mode differences, and interquartile range, then concluded the data as the consensus of the experts. The research findings were as follows: 1. Music resources are trying to meet the goals of their institutes and they are accepted as music learning resources and still develop their educational programs and activities. 2. Lifelong education management in music museums should focus on these aspects. Goals and objective: to collect music instruments and evidences; to promote education and be learning centers; to work as lifelong learning resources. Management: have obvious way in management and human resource development plans; staffs are ready to learn and develop themselves; have marketing plans and approach strategies; curators have knowledge in music; have experts working together; have funding for museum operations. Activities: have varieties of exhibitions (permanent and temporary); always change; let audiences inquire, interpret and learn freely, provide educational spaces; provide data for searching; design participatory learning processes; offer live concerts; mix the display collections, contents and activities together. Evaluation: done individually; not discourage audiences’ appreciation; have many designs for every group of visitors; evaluate visitors’ satisfaction by observation. Connections: connect with other music museum and art groups; share knowledge and collections; connect with foreign music museums; work with artists, musicians and collectors.